Curbing COVID-19: the quest continues in time - Sudhir Bhandari; Ajit Singh Shaktawat; Jitendra Gupta; Shivankan Kakkar; Amitabh Dube (Journal of Ideas in Health, 2020)
The menace of Coronavirus Disease-19 (COVID-19) has made life more and more challenging throughout the world. Amidst these difficult times, doctors have proved their exceptional worth. They have performed their duties with notable dedication, diligence, resilience, and compassion. Here we share our experiences from the State of Rajasthan in Northern India. We were benefitted by very early lockdown by the Government, preventive strategies of containment, and the most effective contact tracing program. The creation of hundreds of surveillance teams and rapid response teams (RRT) was instrumental for the containment program. This was coupled with outstanding medical care exemplified by Sawai Man Singh Medical College Hospital (SMSMCH) at Jaipur, the capital city of Rajasthan. The mortality rate-limiting to 1.98% in Rajasthan has been an outcome of the amalgamation of brisk administrative action, government support, and visionary action and the best of health care facilities. Our COVID-19 management program strategy was based on the advanced treatment guidelines from the Indian Council of Medical Research, New Delhi, India, and the Ministry of Health and Family Welfare, Government of India.